Influence of the antiretroviral therapy on the growth pattern of children and adolescents living with HIV/AIDS - Flávia Jacqueline Almeida; Cristiane Kochi; Marco Aurélio Palazzi Sáfadi (Elsevier, 2019)
Objective: Weight and height growth impairment is one of the most frequent manifestations in HIV-infected children and may be the first sign of disease, being considered a marker of disease progression and an independent risk factor for death. The aim of this review is to evaluate the influence of antiretroviral therapy on the growth pattern of children and adolescents living with HIV/AIDS. Source of data: A non-systematic review was carried out in the PubMed database, with the terms "HIV", "Weight and height growth", "ART" and "children". The most relevant publications were selected. Data Synthesis: Antiretroviral therapy has significantly reduced morbidity and mortality in HIV-infected children and is clearly associated with recovery of weight and height-for-age Z-scores, especially when started early, in the asymptomatic child still without weight-height impairment. Therapeutic strategies involving the GH/IGF-1 axis, especially for children with growth impairment, are still being studied. Conclusions: HIV-infected children show early weight-height impairment; antiretroviral therapy improves the anthropometric profile of these children. Resumo: Objetivo: O acometimento do desenvolvimento pondero-estatural é uma das manifestações mais frequentes nas crianças infectadas pelo HIV e pode ser o primeiro sinal de doença, é considerado um marcador de progressão para doença e um fator de risco independente para morte. O objetivo desta revisão é avaliar a influência da terapia antirretroviral no padrão de crescimento em crianças e adolescentes vivendo com HIV/Aids. Fonte dos dados: Foi feita uma revisão não sistemática na base de dados PubMed, com os termos "HIV", "desenvolvimento pondero estatural", "TARV" e "crianças". Foram selecionadas as publicações mais relevantes. Síntese dos dados: A terapia antirretroviral reduziu substancialmente a morbimortalidade em crianças infectadas pelo HIV e está claramente associada à recuperação do escore-z de peso e de estatura para idade, principalmente quando iniciada precocemente, na criança assintomática e ainda sem comprometimento pondero-estatural. Estratégias terapêuticas que envolvem o eixo GH/IGF-1, principalmente para crianças com comprometimento do crescimento, ainda estão em estudo. Conclusões: As crianças infectadas pelo HIV apresentam comprometimento pondero-estatural precoce e a terapia antirretroviral melhora o perfil antropométrico dessas crianças. Keywords: HIV, Child, Growth, Antiretroviral therapy, Palavras-chave: HIV, Criança, Crescimento, Terapia antirretroviral